2020
DOI: 10.1093/pubmed/fdaa143
|View full text |Cite
|
Sign up to set email alerts
|

Changes of drinking behavior in Korean pregnant women for the last 20 year

Abstract: Background The purpose of this study is to investigate the drinking behavior of Korean pregnant women in 2017 and to compare the changes of drinking status with the results of the research conducted in 1997 and 2008. Methods Pregnant women at one obstetrics and gynecology hospital and one university hospital were the subjects of the study. They were filled out questionnaire. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Fetal alcohol syndrome (FAS) is a congenital fetal disorder caused by maternal alcohol consumption during pregnancy. Children with FAS present with characteristic facial features, growth retardation, and intellectual disability and may even have difficulties adjusting to society later by fetal programming [ 1 3 ]. Alcohol can affect fetal development in various ways, including any amount of alcohol consumed from 3 months before conception to the end of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal alcohol syndrome (FAS) is a congenital fetal disorder caused by maternal alcohol consumption during pregnancy. Children with FAS present with characteristic facial features, growth retardation, and intellectual disability and may even have difficulties adjusting to society later by fetal programming [ 1 3 ]. Alcohol can affect fetal development in various ways, including any amount of alcohol consumed from 3 months before conception to the end of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lee et al [ 9 ], approximately 16% of women were reported to drink alcohol during pregnancy, and 1.7% reported binge drinking in Korea. Moreover, the annual drinking rate among Korean women (over 19 years old) was higher in 2015 (70.8%) than in 1998 (59.3%) according to data from the Korea Health Promotion Institute [ 1 ]. The increasing rate of child-bearing-aged women who consume alcohol can be considered to increase the chance of alcohol exposure during pregnancy, whether intentionally or unintentionally.…”
Section: Introductionmentioning
confidence: 99%